An Analysis of School Climate at An Islamic Junior High School in Indonesia - Putri, Nindina Julita; Hasanah, Uswatun; Annisa, Mutia; Novita, Dian (Procedia of Social Sciences and Humanities, 2024)
People can develop their skills, realize their full potential, and acquire the knowledge they need to achieve their goals in life through education. School climate as one of the components of education can affect the students’ academic success. The study aims at examining the implementation of physical dimension as one of the school climate aspects in one of the Islamic Junior High School in Sidoarjo, East Java, Indonesia. The present study utilizes descriptive qualitative research design by using observation and interview as the research instuments. The results of the study show that the school has implemented clearly stated policies, consistent and unambiguous consequences for violations, and a sense of physical safety within the school. It provides a strong foundation for positive learning and interaction, so that students feel comfortable and safe at schools. Therefore, it leads to positive students' learning experiences as well as the atmosphere and culture of the school.